INNOVATIVE MANAGEMENT IN AIRLINES - D. A. Sidorov (Научный вестник МГТУ ГА, 2016)
The issues of innovation strategy selection, innovative planning system formation, innovative activity organization, creative activity of personnel are considered. The specific features of airlines innovative activity, the structure of innovative process at aviation enterprise are defined.